Lactobacillus plantarum SAL delays aging-associated oxidative stress and gut microbiota dysbiosis in mice - Dong, Wen; Lun, Yongzhi; Sun, Jie; Liu, Ben (Frontiers in Microbiology, 2025)
IntroductionLactobacillus plantarum SAL, isolated from multidrug-resistant patients’ feces, exhibits superior in vitro probiotic traits including bile salt resistance, gastric acid tolerance, and potent antioxidant capacity. While Lactobacillus plantarum generally enhances gut microbiota structure/function, improving health and lifespan in model organisms, the in vivo effects, mechanisms, and potential anti-aging properties of the SAL strain remain unexplored. This study addresses this critical research gap.MethodsTwenty-four SPF KM male mice were divided into a control group (CON), model group (MOD), and a SAL strain intervention group (SAL). MOD and SAL groups received d-gal-induced aging models. SAL group was orally administered SAL strain suspension daily, while MOD and CON groups received saline for 10 weeks. After the intervention, serum and liver tissues were collected to detect aging biomarkers (β-galactosidase) and oxidative stress markers.Colon tissue histopathological examination was performed, and fresh fecal samples were subjected to metagenomic sequencing and analysis. Additionally, Spearman correlation analysis was conducted to evaluate the relationships between genuslevel differential gut microbiota and oxidative stress markers in serum and liver tissues.ResultsCompared with the MOD group, the SAL group exhibited significantly reduced MDA levels in serum and liver tissues (all p < 0.05), elevated activities of SOD and T-AOC (all p < 0.05), and increased serum GSH-Px and CAT activities (all p < 0.05). Colon histology showed structural improvements, including increased crypt numbers, restored architecture, reduced submucosal space, and upregulated expression of ZO-1, Occludin, and Muc2 (all p < 0.05). Gut microbiota analysis revealed increased abundances of Firmicutes and Verrucomicrobia, decreased Bacteroidetes, and elevated Firmicutes/Bacteroidetes (F/B) ratio (p < 0.05). Differential genera Lactobacillus and Mucispirillum showed significant negative correlations with MDA levels (all p < 0.05), while Lactobacillus positively correlated with SOD, GSH-Px, and T-AOC activities.DiscussionThe SAL strain intervention significantly improved redox homeostasis, restored intestinal barrier integrity, and reversed gut dysbiosis, highlighting its dual regulatory role in anti-aging mechanisms. These findings demonstrate the potential of L. plantarum SAL as an anti-aging probiotic and establish a theoretical framework for microbiota - targeted interventions to alleviate age-related pathologies.